2003
DOI: 10.1002/jmri.10378
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varying spectral resolution on the quality of high spectral and spatial resolution magnetic resonance images of the breast

Abstract: Purpose:To evaluate the effect of varying spectral resolution on image quality of high spectral and spatial resolution (HiSS) images. Materials and Methods:Eight women with suspicious breast lesions and six healthy volunteers were scanned using echo-planar spectroscopic imaging (EPSI) at 1.5 Tesla with 0.75-to 1-mm in-plane resolution and 2.3-to 2.6-Hz spectral resolution. Time domain data were truncated to obtain proton spectra in each voxel with varying (2.6 -83.3 Hz) resolution. Images with intensity propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 41 publications
(29 reference statements)
1
40
0
Order By: Relevance
“…It has been demonstrated that, with newer equipment (a GE SIGNA TM 1.5 T whole-body clinical scanner equipped with high-performance self-shielded gradient coils), EPSI data can be acquired at very high spectral and spatial resolution without distortion of water spectra from small voxels. 17,18 The data acquired from human breast with modern scanners often show complicated water spectra with multiple components in small voxels. 17,18 It is likely that, with improved equipment, results of similar quality can be obtained for rodent prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that, with newer equipment (a GE SIGNA TM 1.5 T whole-body clinical scanner equipped with high-performance self-shielded gradient coils), EPSI data can be acquired at very high spectral and spatial resolution without distortion of water spectra from small voxels. 17,18 The data acquired from human breast with modern scanners often show complicated water spectra with multiple components in small voxels. 17,18 It is likely that, with improved equipment, results of similar quality can be obtained for rodent prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The data acquired from human breast with modern scanners often show complicated water spectra with multiple components in small voxels. 17,18 It is likely that, with improved equipment, results of similar quality can be obtained for rodent prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fourier component images from HiSS data allow for isolation of signals from predominately water-based fibroglandular tissue and fatty regions, demonstrating better spectral resolution than mDixon methods 57,58 and more complete fat signal suppression than T1-weighted methods. 59,60 Earlier work showed that HiSS is a potentially useful noncontrast imaging method for breast lesion detection and characterization, [61][62][63][64][65] showing similar performance levels [from a receiver operating characteristic (ROC) analysis] with DCE-MRI 63 in the task of distinguishing between cancer and noncancer cases. In this work, we expand the application of noncontrast HiSS breast MRI to the quantitative assessment of breast density.…”
Section: Introductionmentioning
confidence: 99%
“…High spectral and spatial resolution (HiSS) MR imaging has been used to separate water and fat spectra for detection of breast cancers, 8,9 and images of T 2 * in murine mammary cancer were calculated from the water resonance in each voxel. 10,11 Alternatively, the T 2 * can be measured by analyzing a train of gradient echoes in the time domain. This approach is particularly useful when the proton free induction decay (FID) is sampled unevenly and=or for a relatively short period of time.…”
Section: Introductionmentioning
confidence: 99%